Prevalensi early childhood caries dan severe early childhood caries pada anak prasekolah di Gunung Anyar Surabaya (The prevalences of early childhood caries and severe early childhood caries in preschool children at Gunung Anyar Surabaya) - Rahel Wahjuni Sutjipto; Herawati Herawati; Satiti Kuntari (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2014)
Background: Early childhood caries (ECC) is a serious health problem especially in young children. Frequent night time bottle feeding with milk and prolong breast-feeding are reported to be the possible cause. Purpose: The purpose of study was to determine the prevalence of ECC and severe early childhood caries (SECC) in children at Preschool Gunung Anyar district Surabaya. Methods: The subjects were 65 children consist of children aged 6 months (5 children), 1 year (8 children), 2 years (24 children), and 3 years (28 children). All tooth surface is evaluated. If there was one or more DMFs, it was indicated as ECC, whereas if there was one or more DMFs on smooth surfaces, then indicated as SECC. Results: No caries has found in 6 months and 1 year old children. The higher prevalence of ECC and SECC is in 3 years old children. The most caries was found on mesial maxillary central incisors. Conclusion: This study shows that the prevalence of ECC in group of children aged 6 months - 3 years at Gunung Anyar Surabaya was 30.8 % , while the prevalence was 29.2 % SECC .Latar belakang: Karies anak usia dini merupakan masalah kesehatan yang serius terutama di kalangan anak-anak. Sering mengkonsumsi susu melalui botol pada malam hari dan pemberian ASI yang berkepanjangan dilaporkan sebagai faktor penyebab. Tujuan: Penelitian ini bertujuan untuk meneliti prevalensi ECC dan SECC pada kelompok anak di PAUD Gunung Anyar Surabaya. Metode: Subyek penelitian ini adalah 65 anak yang terdiri dari anak usia 6 bulan (5 anak), 1 tahun (8 anak), 2 tahun (24 anak), dan 3 tahun (28 anak). Semua permukaan gigi dievaluasi. Apabila terdapat 1 atau lebih dmfs, maka diindikasikan sebagai ECC, sedangkan apabila terdapat 1 atau lebih dmfs pada permukaan gigi yang halus, maka diindikasikan sebagai SECC. Hasil: Tidak ditemukan karies pada kelompok anak usia 6 bulan hingga 1 tahun. Prevalensi tinggi ECC dan SECC ditemukan pada kelompok anak usia 3 tahun. Area gigi yang paling sering terkena karies adalah bagian mesial geligi insisif sentral rahang atas. Simpulan: Penelitian ini menunjukkan bahwa prevalensi ECC pada kelompok anak usia 6 bulan-3 tahun dikawasan Gunung Anyar Surabaya adalah 30,8%, sedangkan prevalensi SECC adalah 29,2%.